Effects of bank capital requirement tightenings on inequality - Sandra Eickmeier; Benedikt Kolb; Esteban Prieto (Deutsche Bundesbank, 2018)
We use a newly constructed narrative measure of regulatory bank capital requirement tightening events (Eickmeier et al., 2018) to examine their effects on household income and expenditure inequality in the US. Income and expenditure inequality both decline (the latter decline being slightly less pronounced than the former). Financial income strongly drops after the regulatory events. Richer households tend to be more exposed to financial markets. Hence, their income and expenditures decline by more than those of poorer households. The monetary policy easing after the regulation is shown to contribute to the decline in inequality at longer horizons, as it cushions the negative effects of the capital requirement tightenings on wages and salaries in the medium run, which represent a considerable share of income for lower- to middle-income households.
Keywords: G28; G18; C32; E44; 330; Narrative Approach; Bank Capital Requirements; Local Projections; Inequality